The new strategic brand management : advanced insights and strategic thinking - Kapferer, Jean-Noël (Kogan Page, 2012)
"Adopted internationally by business schools, MBA programmes and marketing practitioners alike, The New Strategic Brand Management is simply the reference source for senior strategists, positioning professionals and postgraduate students. Over the years it has not only established a reputation as one of the leading works on brand strategy but also has become synonymous with the topic itself. The new edition builds on this impressive reputation and keeps the book at the forefront of strategic brand thinking. Revealing and explaining the latest techniques used by companies worldwide, author Jean-Nol͡ Kapferer covers all the leading issues faced by the brand strategist today, supported by an array of international case studies. With both gravitas and intelligent insight, the book reveals new thinking on topics such as putting culture and content into brands, the impact of private labels, the new dynamics of targeting and the comeback of local brands"--